Stories in light : a guide to the stained glass of the basilica at the University of Notre Dame - Cavadini, Nancy (University of Notre Dame Press, 2020)
"The Basilica of the Sacred Heart at the University of Notre Dame contains one of the largest collections of late nineteenth-century French stained glass outside of France. The French Gothic-inspired church has forty-four large stained glass windows containing two hundred and twenty scenes. Today, more than 100,000 visitors tour the basilica each year to admire its architecture or participate in the beautiful liturgies. Honoring both the Sacred Heart and the Virgin Mary, the vibrant windows have, for more than a century, drawn visitors and worshippers alike into a conversation with the art and faith found in the windows. This informative and conveniently sized guidebook tells the unique story of the windows: the improbable creation of a glassworks by cloistered Carmelite nuns in LeMans, France, and their stained glass that so perfectly illuminated the late nineteenth-century French Catholic spirituality of the Congregation of Holy Cross, who established the University of Notre Dame. The words of Father Edward Sorin, CSC, founder of the university, are featured throughout the text. He saw the basilica and its windows as an avenue for teaching this spirituality. The book describes the windows according to their location in the building, from the narthex at the entrance to the Lady Chapel behind the altar. Full-color photographs provide a detailed view of the scenes found in each window. These photos are accompanied by informed commentary on the historical and theological importance of the windows, the iconography of featured saints, and how they illuminate the work of the Holy Cross to educate both mind and spirit. Stories in Light is an easy-to-read book written for all who visit the basilica, including faculty, students, alumni, and friends and family of Notre Dame, and for readers everywhere who want to know more about the rich history and heritage of the Basilica of the Sacred Heart's stained glass"--